Свобода в літературі метамодерного світу: український вимір - Гребенюк, Тетяна Володимирівна; Гребенюк, Т. В.; Grebeniuk, T. V. (Харківський національний університет імені В. Н. Каразіна, 2018)
Об’єктом уваги в статті є метамодернізм як сукупність культурно-естетичних тенденцій і найпоширеніші в сучасному українському суспільстві метанаративи, функціонування яких пов’язане з концептом свободи. Розглядаються метанаративи соціальної користі культурних явищ, персональної причетності людини до життя суспільства і впливу історичної пам’яті на сучасні події. Основним художнім матеріалом дослідження є твори «Інтернат» С. Жадана, «Забуття» Т. Малярчук, «Фелікс Австрія» С. Андрухович, збірка «І тим, що в гробах» А. Бондаря. Объектом внимания в статье является метамодернизм как совокупность культурно-эстетических тенденций и наиболее распространенные в современном украинском обществе метанарративы, функционирование которых связано с концептом свободы. Рассматриваются метанарративы социальной полезности культурных феноменов, персональной причастности человека к жизни общества и влияния исторической памяти на современные события. Основным художественным материалом исследования являются произведения «Интернат» С. Жадана, «Забвение» Т. Малярчук, «Феликс Австрия» С. Андрухович, сборник «И тем, что в гробах» А. Бондаря. Subjects of attention in the article are metamodernism as a set of cultural-aesthetical tendencies and the most widespread in the contemporary Ukrainian society grand narratives that function in tight connections with the concept of freedom. Grand narratives of the public benefit of the cultural phenomena, of the personal participation in the social life and of the historical memory influence on the nowadays events are considered. The postmodern discourse assumed as a basis a set of the features associated with freedom: pluralism, tolerance, liberalism. The above mentioned grand narratives bring into question this freedom. The meta-narrative of the public benefit of the cultural phenomena become apparent in the literature context as an idea of the social mission of the literary and artistic activity. The idea of the personal participation in the social life has its most vivid reflection in the texts devoted to the political and military subject area. The chronotop of the past epochs utterly appeals contemporary writers carrying out a set of the aesthetical-ideological tasks one of which is reconsideration of the usual stereotypes of the historical knowledge. Works “The Boarding School” by Serhij Zhadan, “Oblivion” by Tania Maliarchuck, “Felix Austria” by Sophia Andrukhovych, the prose collection “And to Them, in the Graves” by Andrij Bondar are the material of the investigation.
Свобода в литературе метамодерного мира: украинское измерение
Freedom in the Metamodern World Fiction: the Ukrainian Dimension
Keywords: Українська література; постмодернізм; метамодернізм; метанаратив; свобода; постмодернизм; метамодернизм; postmodernism; metamodernism; metanarrative; freedom